2018
DOI: 10.1002/solr.201700233
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Photo‐Thermal Conversion Properties of Hierarchical Titanium Nitride Nanotube Mesh for Solar Water Evaporation

Abstract: Hierarchical TiN nanotube mesh (HTNM) is prepared by calcining TiO2 nanotube mesh (TONM) in NH3 flow where the TONM is fabricated by electrochemical anodic oxidation of Ti mesh. Calcining temperature affects not only phase composition but also morphology of the HTNM, which further affects its optical absorption and solar water evaporation conversion efficiency (η). The η can reach to 85.36% under 2.5 kW m−2 simulated solar irradiation because HTNM efficiently utilizes solar light. Moreover, it can be reutilize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 38 publications
0
25
0
Order By: Relevance
“…Chalcogenides, nitrides or pnictogenides have recently appeared as promising candidates for photothermal catalysis owing to their capability to transform light into heat. [303][304][305] (d) The investigation of long-term stability of photocatalysts remains insufficient, as most of the stability tests are limited to several hours. For an adequate scale-up to commercial plants, feasible and stable photocatalysts are required.…”
mentioning
confidence: 99%
“…Chalcogenides, nitrides or pnictogenides have recently appeared as promising candidates for photothermal catalysis owing to their capability to transform light into heat. [303][304][305] (d) The investigation of long-term stability of photocatalysts remains insufficient, as most of the stability tests are limited to several hours. For an adequate scale-up to commercial plants, feasible and stable photocatalysts are required.…”
mentioning
confidence: 99%
“…[ 1–9 ] Titanium nitride (TiN), zirconium nitride (ZrN), and other plasmonic nitrides such as hafnium nitride (HfN) and tantalum nitride (TaN) are particularly attractive due to their high melting points that bolster stability at higher ambient temperatures [ 10–12 ] and/or under higher laser irradiation intensities, [ 13–16 ] in addition to their mechanical hardness [ 17,18 ] and complementary metal‐oxide‐semiconductor compatibility. [ 19–21 ] Recent work has demonstrated that TiN shows strong local heating compared to Au, [ 22–24 ] which may be exploited for photothermal therapy, [ 25,26 ] shape‐memory effects, [ 27 ] thermochromic windows, [ 28 ] photoreactions, [ 29–32 ] heat transducers or thermophotovoltaic materials, [ 22,33–37 ] or photodetection. [ 38 ] Implicit in these observations and devices are very different optical responses of metallic nitrides compared to gold—the most similar classical plasmonic material—particularly with regard to the dissipation of heat.…”
Section: Introductionmentioning
confidence: 99%
“…Once 1 kW m −2 simulated sun light irradiated on these samples, vapor generated immediately with the mass changed with time as shown in Fig. 5a and c. The solar-vapor conversion efficiency (η) can be calculated by Equation (2) [19].…”
Section: Resultsmentioning
confidence: 99%
“…In order to enhance solar evaporation conversion efficiency, it is necessary to combine high-efficiency PTC materials with a substrate for heat insulation and liquid supply. PTC materials for heating and evaporating water include plasmonic metals [14][15][16][17][18] and ceramic nanomaterials [19], carbon-based materials [20][21][22][23][24][25] and semiconducting nanomaterials [26,27]. For instances, Chen et al [28] reported a dualfunctional asymmetric plasmonic structure formed by silver nanoparticles and porous templates.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation